Vibration Fracture Mechanism and Optimization Design of Array Power Supply for Near-Space SAR - Changrui Wang; Lina Tang; Henghai Wang (Shock and Vibration)
The random vibration failure of an array power supply for near-space SAR was analyzed. The fracture mechanism and the fracture reason of fracture formation in the specimen were investigated. The results show that antishock MOS pin breaks first, and the power supply is still in the working state during the process of random vibration. This caused dischargings at the tip of the fracture and melting of the tip of the broken pin which form a river-shaped fracture and granular tissue. The plastic fracture with typical dimple morphology of the pins for the resistor tube occurred during the random vibration. The intergranular fracture appeared at the welding part of the electronic components for array power supply, which presented a brittle fracture mechanism. The fracture was dominated by a ductile fracture for components when the stress produced by the vibration was close to the yield strength of the material. The fracture was dominated by a brittle fracture for components when the stress produced by the vibration was far beyond the yield strength of the material. A simulation evaluation system based on the high-confidence model was proposed. The stress of the electronic components for array power supply and its welding was much lower than the allowable strength of the material by the optimization of the structure and the form of the welding for the array power supply. The sample was successfully tested and verified without any further fracture problems.